2021
DOI: 10.1108/reps-05-2021-0053
|View full text |Cite
|
Sign up to set email alerts
|

How can tax compliance be incentivized? An experimental examination of voice and empathy

Abstract: PurposeTax evasion is an economic crime that nearly all world countries suffer from. Its consequences are countless, including poor public spending on infrastructure projects and social welfare programs, low economic growth and development, institutional mistrust and fiscal deficits. For developing countries in particular, targeting development programs and infrastructural investments requires an efficient tax collection policy to generate sufficient funds for such purposes. This makes the tax evasion problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…It was found that the default assignments succeeded in changing the employees' spending and savings attitude (Blumenstock et al, 2018). In the same vein, an experimental approach testing the impact of two behavioral primes on tax compliance behavior: 1) having a voice in the allocation of tax, 2) triggering empathy in public spending found both primes statistically significant and had a positive impact on the willingness of subjects to comply (AbdelNabi et al, 2022). Indeed, the nudging approach has proven to be an efficient method in several policy areas as it is a low-cost intervention method that does not limit the choice of people and succeeds to change the attitudes of people.…”
Section: Nudging Paternalism and Cognitive Biasesmentioning
confidence: 96%
“…It was found that the default assignments succeeded in changing the employees' spending and savings attitude (Blumenstock et al, 2018). In the same vein, an experimental approach testing the impact of two behavioral primes on tax compliance behavior: 1) having a voice in the allocation of tax, 2) triggering empathy in public spending found both primes statistically significant and had a positive impact on the willingness of subjects to comply (AbdelNabi et al, 2022). Indeed, the nudging approach has proven to be an efficient method in several policy areas as it is a low-cost intervention method that does not limit the choice of people and succeeds to change the attitudes of people.…”
Section: Nudging Paternalism and Cognitive Biasesmentioning
confidence: 96%
“…The problem of tax evasion and fraud was analyzed by Stankevicius and Leonas (2015) and was treated in a hybrid model approach with the outcome that tax evaders must be analyzed also through psychological and social portraits. The usage of empathy and voice in the tax evasion problem was analyzed by AbdelNabi et al (2021) with the assessment that the experimental and behavioral approach of citizens' incentives can be a factor that underlies the fight against tax evasion. The dichotomy between fraud and legal aspects of tax evasion was debated also by Opreț et al (2017) on the necessity of creating a common legal framework, especially at the EU level; the authors suggest that they are several factors that must be considered: accounting information and mechanisms and illicit practices.…”
Section: Tax Evasion Problemsmentioning
confidence: 99%
“…The Influence of Perceptions of Justice and Trust toward Government on Tax Compliance (Case Study on Msme Taxpayers in Surabaya) [1] Agus Arianto Toly, S.E., M.S.A., Ak, [2] Angelita Ananda Peery, [3] Anastasya Ellen Wijaya [1] Petra Christian University, [2] Petra Christian University, [3] Petra Christian University [1] agustoly@petra.ac.id, [2] peeryangelita@gmail.com, [3] anastasyameme123@gmail.com significantly contribute to state income. It is because MSMEs are also tax objects, so MSME owners are tax subjects obliged to pay taxes every period.…”
Section: Grafik Pendapatan Pajak 2019 -2022mentioning
confidence: 99%
“…Tax justice is implementing the existing tax system, which is running as it should, following applicable regulations, and upholding the principle of equality in providing attitudes toward taxpayers (Soon, 2017). Tax policies or regulations will create the perception that taxes are fair for everyone and are accommodative so that they will encourage taxpayer compliance (Abdelnabi et al, 2022). Therefore, it is very important to carry out measures that can lead to tax compliance to increase public compliance (Cologna et al, 2022).…”
Section: Table 1 Total Of Msme Taxpayers In All Tax Offices In Surabayamentioning
confidence: 99%
See 1 more Smart Citation